Involvement of nitric oxide in the jasmonate-dependent basal defense against root-knot nematode in tomato plants - Zhou, Jie; Jia, Feifei; Shao, Shujun; Zhang, Huan; Li, Guiping; Xia, Xiaojian; Zhou, Yanhong; Yu, Jingquan; Shi, Kai (Frontiers in Plant Science, 2015)
Jasmonic acid (JA) and nitric oxide (NO) are well-characterized signaling molecules in plant defense responses. However, their roles in plant defense against root-knot nematode (RKN, Meloidogyne incognita) infection are largely unknown. In this study, we found that the transcript levels of the JA- and NO-related biosynthetic and signaling component encoding genes were induced after RKN infection. Application of exogenous JA and sodium nitroprusside (SNP; a NO donor) significantly decreased the number of egg masses (EMs) in tomato roots after RKN infection and partially alleviated RKN-induced decreases in plant fresh weight and the leaf net photosynthetic rate. These molecules also alleviated RKN-induced increases in root electrolyte leakage and membrane peroxidation. Importantly, NO scavenger partially inhibited JA-induced RKN defense. The pharmacological inhibition of JA biosynthesis significantly increased the plants’ susceptibility to RKNs, which was effectively alleviated by SNP application, showing that NO may be involved in the JA-dependent RKN defense pathway. Furthermore, JA and SNP both induced increases in protease inhibitor 2 (PI2) gene expression after RKN infestation. Silencing of PI2 compromised both JA- and SNP-induced RKN defense responses, suggesting that the PI2 gene mediates JA- and NO-induced defense against RKNs. This work will be important for deepening the understanding of the mechanisms involved in basal defense against RKN attack in plants.